Effectiveness of piezoelectric versus straight hand piece at low speed within the surgical extraction of retained lower third molars - Morales-Sambachi, Bryan (2022)
Objective: Determine the effectiveness of the piezoelectric handpiece vs. the straight handpiece at low speed in surgeries of impacted lower third molars, in relation to post-surgical effects (edema, pain and trismus) and the operative time of the osteotomy, in patients attending the Maxillofacial Surgery Service of the “Hospital de Especialidades Fuerzas Armadas N°1”. Method: It is an observational, longitudinal prospective cohort clinical study. A sample of 40 patients of both sexes aged between 18 and 25 years was taken, divided into two groups of 20 patients each, in group A extractions were performed with piezoelectric and in group B with straight rotary handpiece at low velocity. The results were analyzed on the third, fifth and eighth day, the edema was measured with the method of Amin and Laskin, for the pain the Visual Analogous Scale (VAS) was used, and for the presence of trismus with the instrument foot of king.  Results: In group A, edema (11.72 mm), pain (4.67) and mouth opening (39.49 mm) were lower than in group B edema (12.29 mm), pain (4.8) and mouth opening (35.83 mm) and osteotomy time was significantly longer with piezoelectric (6.54 ± 3.05 min) compared to the straight handpiece (1.55 ± 0.57 mm). min) and there was a difference in edema, pain and trismus under normal conditions in contrast to what was obtained at 3, 5, 8 days between the two instruments. Conclusion: the post-surgical effects of edema, pain and trismus of the extraction of retained lower third molars are less intense with the piezoelectric compared to the straight handpiece, the use of the piezoelectric being recommended.